2017
DOI: 10.1097/aog.0000000000001931
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Hyperoxemia and Risk of Neonatal Morbidity

Abstract: Objective To test the hypothesis that intrauterine hyperoxemia is associated with an increased risk of neonatal morbidity. Methods This was a secondary analysis of a prospective study of singleton, non-anomalous deliveries at or beyond 37° weeks at an institution with universal umbilical cord gas policy from 2010 to 2014. The primary outcome was a composite of neonatal morbidity including neonatal death, meconium aspiration syndrome, intubation, mechanical ventilation, hypoxic-ischemic encephalopathy, and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Composite morbidity (mechanical ventilation, hypothermic therapy, meconium aspiration, and death) was significantly increased in neonates with both hyperoxia and acidemia compared with nonacidemic hyperoxic infants. 9 This is further supported by reports of an increased need for neonatal resuscitation and a fourfold increase in umbilical cord pH of less than 7.2. 10 While intrauterine and extrauterine life certainly differ, these findings align with the pediatric literature that supports neonatal resuscitation with room air rather than 100% oxygen.…”
Section: Fetal Acidemia and Neonatal Morbiditymentioning
confidence: 80%
See 1 more Smart Citation
“…Composite morbidity (mechanical ventilation, hypothermic therapy, meconium aspiration, and death) was significantly increased in neonates with both hyperoxia and acidemia compared with nonacidemic hyperoxic infants. 9 This is further supported by reports of an increased need for neonatal resuscitation and a fourfold increase in umbilical cord pH of less than 7.2. 10 While intrauterine and extrauterine life certainly differ, these findings align with the pediatric literature that supports neonatal resuscitation with room air rather than 100% oxygen.…”
Section: Fetal Acidemia and Neonatal Morbiditymentioning
confidence: 80%
“…This is exactly what Raghuraman and colleagues demonstrated in a large prospective cohort analysis. 9 While there was no difference in neonatal morbidity between those receiving oxygen and those on room air, there was a significant difference among infants with acidemia and hyperoxia. Composite morbidity (mechanical ventilation, hypothermic therapy, meconium aspiration, and death) was significantly increased in neonates with both hyperoxia and acidemia compared with nonacidemic hyperoxic infants.…”
Section: Fetal Acidemia and Neonatal Morbiditymentioning
confidence: 93%
“…Samples were considered paired if the cord pH was at least 0.02 lower in the artery than the vein. 6,14,15 Data regarding maternal demographics, antenatal course, intrapartum events, and neonatal diagnoses were extracted from medical records by trained research staff. The primary outcome in assessing the predictive ability of umbilical cord oxygen content was a composite of neonatal morbidity that included intubation, mechanical ventilation, meconium aspiration syndrome, hypoxic-ischemic encephalopathy, need for hypothermia treatment, and neonatal death.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome in assessing the predictive ability of umbilical cord oxygen content was a composite of neonatal morbidity that included intubation, mechanical ventilation, meconium aspiration syndrome, hypoxic-ischemic encephalopathy, need for hypothermia treatment, and neonatal death. 6,14,16 Only one diagnosis was counted per patient. The diagnosis of meconium aspiration syndrome was made by neonatal respiratory distress in the setting of meconium stained amniotic fluid and associated radiographic abnormalities.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, for early and accurate detection of the health status of newborns, a complete approach would include both the UA and UV sampling. Studies on differences between UA and UV pH showed that pH, measured in the UA can give valuable information and is useful in predicting the neonatal outcome in term infants (8,9). There is a lack of evidence reporting differences between UA and UV in preterm newborns.…”
Section: Introductionmentioning
confidence: 99%